2015
DOI: 10.1093/nar/gkv379
|View full text |Cite
|
Sign up to set email alerts
|

Repression of hypoxia-inducible factor α signaling by Set7-mediated methylation

Abstract: Hypoxia-inducible factor (HIF)-1α and HIF-2α are the main regulators of cellular responses to hypoxia. Post-translational modifications of HIF-1α and 2α are necessary to modulate their functions. The methylation of non-histone proteins by Set7, an SET domain-containing lysine methyltransferase, is a novel regulatory mechanism to control cell protein function in response to various cellular stresses. In this study, we show that Set7 methylates HIF-1α at lysine 32 and HIF-2α at lysine K29; this methylation inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 100 publications
(117 reference statements)
1
91
1
Order By: Relevance
“…Liu and co-workers25 recently showed that HIF1 alpha and HIF2 alpha are methylated by SETD7 on lysines 32 and 29, respectively. This methylation inhibits the expression of HIF1/2 target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and co-workers25 recently showed that HIF1 alpha and HIF2 alpha are methylated by SETD7 on lysines 32 and 29, respectively. This methylation inhibits the expression of HIF1/2 target genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the classification may not be accurate, because some agents target more than one mechanism and it may be inappropriate to include them in a definite category. The targets and mechanisms of HIF inhibitors (Table 1) and some evaluated in clinical trials [Data were obtained from National Clinical Trial (https://clinicaltrials.gov)] are summarized 3031323334353637383940414243444546474849505152535455…”
Section: Hif Inhibitors For Cancer Therapymentioning
confidence: 99%
“…2-methoxyestradiol (2ME2) is a product of estrogen metabolite and naturally produced by catechol-O-methyltransferase-mediated O-methylation of 2-hydroxyestradiol. 2ME2 was initially considered to disrupt microtubules, and later found to inhibit synthesis of HIF-1α and HIF-2α proteins, and suppress their nuclear translocation and transcriptional activity 3536. In ongoing phase II trials, 2ME2 is administered alone or in combination with other agents to treat various advanced or metastatic solid tumors (NCT00592579, NCT00481455, and NCT0044431).…”
Section: Hif Inhibitors For Cancer Therapymentioning
confidence: 99%
“…SET7/9 is also enriched at the hypoxia response elements of a subset of HIF-1 regulated genes LDHA , HK2 , and PDK1 , and increases transcription of these glycolytic genes in hypoxic cells [44]. In contrast, Xiao and his colleagues recently showed that SET7/9 directly induces monomethylation of HIF-1α at K32 and of HIF-2α at K29, leading to suppression of HIF transcriptional activity without affecting their protein levels [45]. Knockdown of SET7/9 increases HIF-1α binding to the hypoxia response element to promote HIF-1 transcriptional activity and expression of the glycolytic genes in human clear cell renal carcinoma RCC4 cells, thereby increasing glucose uptake and ATP production.…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 99%